Meningkatkan Hasil Belajar Peserta Didik Kelas VIII SMP Negeri 3 Satap Maba Menggunakan Model Pembelajaran Problem Based Learning (PBL) Pada Konsep Bahasan Cahaya - Muhrin, Lisna (Program Studi Pendidikan Fisika STKIP Kie Raha Ternate, 2023)
This research is a classroom action research that aims to find out whether the application of the problem based learning (PBL) learning model can improve the learning outcomes of physics students in class VIII students of SMP Negeri 3 Satap Maba. The subject of this study was class VIII SMP Negeri 3 Satap Maba, which consisted of 25 students. This research was conducted in 2 cycles consisting of 4 components, namely: planning, implementation, observation and reflection. Collecting data by means of observation, evaluation and tests at the end of each teaching cycle; analyze the data through the results of qualitative analysis. Based on the results of class VIII action research at SMP Negeri 3 Satap Maba which was carried out and produced, namely the results obtained by students in cycle I showed an increase compared to before being given learning by applying the Problem Based Learning learning model to Light material. After learning by using the learning model the results increased from 24% to 75%. In cycle II, the learning outcomes of students using the problem-based learning model also showed an increase of 100% with an average value of 72.12%.